Psychoeducation Program for Parents of Children with Special Needs in The Autistic Category - syarifah Ivonesti; Nina Zakiah; Ade Silvana; Sri Ika Mulia (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
The purpose of community service is to provide assistance to increase the acceptance of parents of children with special needs in the Autistic category. The method used is Psychoeducation. Psychoeducation is a method carried out to increase the acceptance of parents of Children with Special Needs in the Autistic Category. The participants in the dimming activity were parents of Children with Special Needs in the Autistic category, totaling 25 participants. Service participants have a pre-score, which is a low category in terms of parental acceptance. The method of psychoeducational activities consists of three main stages, as well as evaluation. In the preparation stage, the team first analyzed the needs of psychoeducation by conducting interviews with parents who have children with special needs in the Autistic category. Then, at the implementation stage, the activity included the delivery of material about parental acceptance of autistic children, the definition of Autism, the factors that cause Autism, sharing of the problems faced, and discussions. The results of the evaluation of this psychoeducational activity showed an increase in the average score from 22.40 in the pre-test to 67.20 in the post-test. Psychoeducation makes a positive contribution to the acceptance of parents of Children with Special Needs of autistic children. So that with increased acceptance from parents, it can increase the growth and development of autistic children through proper parenting.